The purpose driven life what on earth am I here for? - Warren, Richard 1954- (Grand Rapids, Mich. Zondervan, 2012)
Translated into over 50 languages, The Purpose Driven Life is far more than just a book; it is a guide to a spiritual journey that has transformed millions of lives. Once you take this journey, you'll never be the same again. This new, expanded edition of The Purpose Driven Life, created for a new generation of reader, includes: Video introductions by Rick Warren to chapters 1-42 and an audio Bible study at the end of each chapter, with over 30 additional hours of teaching by Rick Warren (accessible on http://purposedriven.com from links and QR codes at the beginning and end of each chapter). Two new bonus chapters on the most common barriers to living a purpose driven life. Access to an online community where you can discuss your journey to purpose, get feedback, and receive support. On your journey you'll find the answers to 3 of life's most important questions: The Question of Existence: Why am I alive? The Question of Significance: Does my life matter? and the Question of Purpose: What on earth am I here for? Transform your life. Start your journey today.
What on earth am I here for? -- Purpose #1: You were planned for God's pleasure -- Purpose #2: You were formed for God's family -- Purpose #3: You were created to become like Christ -- Purpose #4: You were shaped for serving God -- Purpose #5: You were made for a mission.
Includes bibliographical references.
Keywords: Christian life